The role of the kindergarten building in providing a supportive environment for developing economic concepts among children from the teachers’ point of view - Aldossary, Norah Saleh Abdullah; Etman, Ali Abd Eltawab Mohamed; Omar, Sahar Mansour Sayed (Journal of Posthumanism, 2025)
The study aimed to identify the impact of kindergarten buildings in providing a supportive environment for the development of economic concepts among kindergarten children. The study population and sample consisted of (109) kindergarten teachers in the city of Najran in the Kingdom of Saudi Arabia, who were randomly selected from government kindergarten institutions. The study was conducted during the second semester of the academic year (2024/2025). The descriptive analytical approach was used, as the study included a questionnaire directed at kindergarten teachers to determine the impact of kindergarten buildings in providing a supportive environment for the development of economic concepts among children. The questionnaire included (8) paragraphs related to the role of kindergarten building in providing a supportive environment for the development of children’s economic concepts. The researchers used the theoretical framework, previous studies, and specialized experience in the field of child education to develop the study tools. The results were processed using the SPSS statistical program, and the study reached the following conclusions: The educational building in kindergartens plays a positive and effective role in providing a supportive environment for developing economic concepts among children, from the perspective of kindergarten teachers largely in general. The study also reached some proposals and visions for developing appropriate capabilities and equipment in kindergartens to provide a supportive environment for developing economic concepts among kindergarten children.